Neuroimmune mechanisms in fear and panic pathophysiology - McMurray, Katherine M. J.; Sah, Renu (Frontiers in Psychiatry, 2022)
Panic disorder (PD) is unique among anxiety disorders in that the emotional symptoms (e.g. fear and anxiety) associated with panic are strongly linked to body sensations indicative of threats to physiological homeostasis. For example, panic attacks often present with feelings of suffocation that evoke hyperventilation, breathlessness, or air hunger. Due to the somatic underpinnings of PD, a major focus has been placed on interoceptive signaling and it is recognized that dysfunctional body-to-brain communication pathways promote the initiation and maintenance of PD symptomatology. While body-to-brain signaling can occur via several pathways, immune and humoral pathways play an important role in communicating bodily physiological state to the brain. Accumulating evidence suggests that neuroimmune mediators play a role in fear and panic-associated disorders, although this has not been systematically investigated. Currently, our understanding of the role of immune mechanisms in the etiology and maintenance of panic disorder remains limited. In the current review, we attempt to summarize findings that support a role of immune dysregulation in PD symptomology. We compile evidence from human studies and panic-relevant rodent paradigms that indicate a role of systemic and brain immune signaling in the regulation of fear and panic-relevant behavior and physiology. Specifically, we discuss how immune signaling can contribute to maladaptive body-to-brain communication and conditioned fear that are relevant to spontaneous and conditioned symptoms of PD, and identify putative avenues warranting future investigation.